1995
DOI: 10.1152/jappl.1995.78.5.1733
|View full text |Cite
|
Sign up to set email alerts
|

Human fiber size and enzymatic properties after 5 and 11 days of spaceflight

Abstract: Biopsies from the vastus lateralis muscle were obtained from three astronauts before and after two 5-day flights and from five astronauts before and after one 11-day flight (space shuttle flights: STS-32, -33, and -34). Muscle fibers from two separate samples from each biopsy were classified as type I and II or as type I, IIA, and IIB by using qualitative myofibrillar adenosinetriphosphatase (ATPase) staining. Cross-sectional area (CSA), number of capillaries per fiber, and the activities of succinate dehydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
216
3
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(251 citation statements)
references
References 0 publications
24
216
3
8
Order By: Relevance
“…The ex-pression of IId MHC (most likely analogous to IIx) has also been observed in the rat soleus of 21-and 28-d suspended rats [67]. A similar tendency in fiber type transformation was also seen in the human vastus lateralis muscle after 11 d of spaceflight [77,78] and in the soleus after 4 months of bedrest associated with fiber atrophy [79,80].…”
Section: Fiber Phenotypementioning
confidence: 67%
“…The ex-pression of IId MHC (most likely analogous to IIx) has also been observed in the rat soleus of 21-and 28-d suspended rats [67]. A similar tendency in fiber type transformation was also seen in the human vastus lateralis muscle after 11 d of spaceflight [77,78] and in the soleus after 4 months of bedrest associated with fiber atrophy [79,80].…”
Section: Fiber Phenotypementioning
confidence: 67%
“…LeBlanc et al 75 showed a 6% decrease in muscle volume following an 8-day spaceflight, whereas 6 months of spaceflight seems to result in a 13-17% decrease in muscle mass. 76,77 Following an 11-day human spaceflight, Edgerton et al 78 observed a significant decline in Short-term space flight (17 days) was found to reduce specific tension of soleus muscle fibers. 80 Although human data from Skylab and Mir suggest that leg extensors atrophy and loose peak force faster than flexors, when flight duration is long enough (4200 days) both groups of muscles show similar declines of B30 % in isokinetic strength.…”
Section: Muscle Atrophymentioning
confidence: 99%
“…Furthermore, lipid droplets (white spheres) were more frequent postflight, accompanied by partially lost alignment of sarcomeres of adjacent myofibrils. 78 It is important to note similarities in atrophy and loss of sarcomere alignment between individuals with SCI and astronauts postflight. Although both SCI and spaceflight lead to a decrease in muscle mass, a fundamental difference is believed to exist between disuse and denervation atrophy.…”
Section: Physiological Consequences Of Sci and Microgravitymentioning
confidence: 99%
“…1,27,62,64,69,78,84 For example, inactivity induces substantial atrophy in muscles that play an antigravity, postural role. The antigravity, predominantly slow-twitch type I muscles, such as the soleus, atrophy more than primarily fasttwitch type II muscles and extensor muscles are more affected than flexors.…”
Section: Inactivity and Muscle Massmentioning
confidence: 99%